Literasi Keuangan, Efikasi Keuangan, dan Pengalaman Keuangan Terhadap Perilaku Manajemen Keuangan Pengguna SPayLater DKI Jakarta - Bunga Safira (Administratif Profesional, 2022)
The phenomenon of using Buy Now, Pay Later as a payment method occurs almost all over the world, one of them is Indonesia. The widespread use of Buy Now, Pay Later in the community if it is not accompanied by great financial management behavior, will mischief the community itself, so it is necessary to improve financial management behavior in the community. This research was conducted to determine the effect of financial literacy, financial self- efficacy, and financial experience on the financial management behavior of SPayLater users in Jakarta. The number of samples is 100 respondents. The data collection technique used in this study was a questionnaire. Research data were analyzed using SMART PLS. The results of this study indicate that the financial literacy variable has no effect on financial management behavior with a coefficient value of 0.028 and a P value of 0.383, and the financial self-efficacy variable has a positive effect on financial management behavior with a coefficient value of 0.542 and a P value of 0.000, the financial experience variable has a positive effect on financial management behavior. with a coefficient value of 0.323 and a P value of 0.001. Keywords: Buy Now, Pay Later, Financial Literacy, Financial Self-Efficacy, Financial Experience, Financial Management Behavior